ANALISIS EFISIENSI BANK UMUM KONVENSIONAL DI INDONESIA MENGGUNAKAN METODE DATA EVELOPMENT ANALYSIS (DEA) PADA TAHUN 2014-2018 - Naili Farchah; Ida Savitri Kusmargiani (KEUNIS, 2020)
The purpose of the research is to analayze efficiency level of Commercial Bank in Indonesia (Bank Mandiri, Bank BNI, Bank BRI, Bank BTN, Bank BCA, Bank Danamon, Bank CIMB and Bank PAN) 2014-2018 period with Data Envelopment Analysis (DEA) method. Data used in this research is secondary data taken from Financial Statement Publication issued by Otoritas Jasa Keuangan (OJK) 2014-2018 period.Bank used in this reseach is eight bank which include in BUKU 4. Length of research period is five years from 2014 until 2018. This research uses input and output variable with Data Envelopment Analysis (DEA) method. The result of research in 2014 all bank object efficient. In 2015 and 2016 inefficiency bank is BNI. In 2017 and 2018 inefficiency banks is Mandiri and BNI. Based on invention can be concluded that national foreign exchange private bank (BUSN) more efficiency than government bank in period research